(( Evaluation of the effectiveness of saline solution temperature on complications of surgical impacted mandibular third molars extraction )): hama university (Journal of Hama University, 2024)
(( Evaluation of the  effectiveness of saline solution temperature on complications of surgical impacted mandibular third molars extraction ))PURPOSE: The aim of this research is to evaluate the effect of the temperature of the perfusion fluid used during surgical extraction of the mandibular molars on postoperative complications (edema-pain-bleeding).MATERIALS AND METHODS: The study was contained of 60 impacted lower third molars existed in 30 patients (12 male + 18 female) who had two symmetric impacted lower third molars From Modified Brand rating. (20 Molars used a normal saline serum، 20 Molars used a cooled saline serum، 20 Molars used a warm saline serum)Edema and pain were measured after one، tow and seven days. Bleeding was measured after 24 and 48 hours.  After that the data was statistically studied.RESULTS:There was a significant difference in the edema variable (P
Keywords: Cold saline solution ، Surgical extractions، edema، bleeding، Warm saline solution lower third molars impacted.